Hyperglycemia Prevalence Among Artisans and Workers in Selected Factories In Lagos, Southwest, Nigeria - Yahaya, Tajudeen Olanrewaju; Sifau, Mutiu O; Oladele, Esther O; Bashar, Danlami M; Abubakar, Aminu L; Salisu, Naziru; Usman, Bello M; Koko, Jamilu D (Folia Medica Indonesiana, 2022)
Highlights: • Workplace pollutants predispose people to hyperglycemia through beta cell dysfunction and insulin resistance. • The risk is increased by unhealthy lifestyles such as smoking and drinking. • Aging, due to mitochondrial function decline, also promotes hyperglycemia. Abstract: The increased global prevalence of hyperglycemia is linked partly to increasing industrial emission exposure, necessitating risk evaluations of various categories of workers worldwide. This study measured the blood glucose levels of selected non-obese artisans and workers from three companies (Imperio International, Mouka Foam, and Continental Iron) in Lagos, Nigeria. The participants' demographic data were collected using structured questionnaires, after which their blood glucose levels were measured using a glucometer. The results were compared with the World Health Organization (WHO) standards (88–126 mg/dL). On average, Imperio International participants were 32 years old, Mouka Foam and Continental Iron were 28 years old, and the artisans were 32 years old. Most of the participants were male secondary school graduates who worked an average of nine hours per day, six days a week. Artisans had the highest hyperglycemic population (46.15%), followed by Imperio International and Continental Iron (33% each), and Mouka Foam (29.41%). Smokers accounted for 10.53% of the hyperglycemic population, followed by alcoholics (36.84%), those who drank and smoked (42.11%), and those who did not drink or smoke (10.53%). Age class â‰¥41 accounted for 36.84% of the hyperglycemic population, class 31-40 (34.21%), and class 21-30 (28.95%). Participants with secondary school education constituted 63.16% of the hyperglycemic population, primary education (18.42%), individuals having no education (13.16%), and tertiary education (5.26%). The findings indicate that workplace pollutants predispose workers to hyperglycemia and that smoking and alcohol increase the risks. The findings necessitate exposure reduction and healthy lifestyles in the workplace.